2009
DOI: 10.1038/modpathol.2009.113
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic significance of c-Myc expression in soft tissue leiomyosarcoma

Abstract: The biological potential of soft tissue leiomyosarcoma is difficult to predict using current standard prognostic parameters, and control of systemic disease is challenging with current chemotherapeutic protocols. Additional prognostic markers and alternative treatment options are very much required. Previous studies implicate upregulation of the oncogenic nuclear transcription factor c-Myc with aggressive behavior of many solid tumors. Therefore, this oncoprotein was evaluated as a prognostic marker for overal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
29
0
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(31 citation statements)
references
References 27 publications
1
29
0
1
Order By: Relevance
“…13 In regard to soft tissue sarcomas, MYC overexpression and increased MYC copy numbers are frequent in high-grade chondrosarcomas, 14 epithelioid sarcomas of the proximal type, 15 in higher-grade myxoid liposarcomas, 16 and have an adverse prognostic impact in leiomyosarcomas of soft tissues. 17 A recent study reported MYC high-level gene amplification in postradiation cutaneous angiosarcomas and in chronic lymphedema-associated cutaneous angiosarcomas (so-called secondary angiosarcomas), whereas so-called primary angiosarcomas of skin, soft tissues, bone, and visceral organs were negative. 6 Interestingly, high-level amplification of MYC was found in 55% of secondary angiosarcomas in this study and was not associated with tumor grade and clinical prognosis.…”
Section: Postradiation Angiosarcomamentioning
confidence: 99%
“…13 In regard to soft tissue sarcomas, MYC overexpression and increased MYC copy numbers are frequent in high-grade chondrosarcomas, 14 epithelioid sarcomas of the proximal type, 15 in higher-grade myxoid liposarcomas, 16 and have an adverse prognostic impact in leiomyosarcomas of soft tissues. 17 A recent study reported MYC high-level gene amplification in postradiation cutaneous angiosarcomas and in chronic lymphedema-associated cutaneous angiosarcomas (so-called secondary angiosarcomas), whereas so-called primary angiosarcomas of skin, soft tissues, bone, and visceral organs were negative. 6 Interestingly, high-level amplification of MYC was found in 55% of secondary angiosarcomas in this study and was not associated with tumor grade and clinical prognosis.…”
Section: Postradiation Angiosarcomamentioning
confidence: 99%
“…The c-myc protein is a transcription factor that regulates many downstream factors responsible for cell cycle progression and apoptosis. Over the past couple decades, the oncogenic properties of c-myc have been described in a wide variety of malignancies [7][8][9][10]. Aberrations deregulating c-myc transcription have been implicated in many hematologic malignancies, especially Burkitt lymphoma and diffuse large Bcell lymphoma (DLBCL) [11,12].…”
Section: Introductionmentioning
confidence: 99%
“…It is necessary to select the appropriate therapy for patients with STSs due to their different pathobiological behavior and prognostic significance. A number of prognostic or biological markers were studied in STSs and reported to be significant prognostic markers (5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19).…”
Section: Introductionmentioning
confidence: 99%